Experimental Study of Precast Beam Joints Using Steel Plates in Beam-Column Joints Due to Cyclic Loading - Hanafi Ashad (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
In seismic design, reinforced concrete structures must perform well under heavy load conditions. To withstand large lateral loads without severe damage, structures require strength and energy dissipation capacity. It is generally not economical to design reinforced concrete structures to the greatest possible ground motions without damage. Therefore, the need for ductility must be weighed against economic constraints. This research is focused on dry joints where the joints are on beams in the plastic hinge area and modeled using steel plates, this modeling will be compared with the hysteresis and ductility curves in three types of specimens namely BU-1 without using plate joints, BU-2 using plate joints measuring 300mm x 400mm, BU-3 plate joints measuring 200mm x 400mm, with the same thickness and quality, namely 8mm thick and Fu 370 MPa. To strengthen the use of the plate connection, A325 bolts with a diameter of 12 mm and Fu 620 MPa are used. The results show that the pinching effect is found in the hysteresis curve of the BU-2 and BU-3 specimens. Meanwhile, for the ductility test at peak load, namely the seventh ductility for BU-1, the value is still better than BU-2 and BU-3. These results can still be improved with several variations of plate thickness, for this reason, further studies are recommended to develop and increase recommendations for several variations of plate joints, because precast joints, especially dry joints, are still the focus of research, especially in Indonesia.